2017
DOI: 10.1108/jrim-10-2016-0104
|View full text |Cite
|
Sign up to set email alerts
|

How trust moderates social media engagement and brand equity

Abstract: Purpose The purpose of this paper is threefold: first, to develop and measure customer engagement scale in context to social media (SM); second, to elucidate the variables that impact customers’ brand engagement on SM and its impact in building customer-based brand equity; and finally, to examine the moderating role of trust in SM brand engagement and brand equity relationship. Design/methodology/approach The data were collected from 767 SM users working in multinational corporations of Gurgaon city, using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 61 publications
3
107
0
5
Order By: Relevance
“…However, there are other indicators, such as engagement, that measure the level of people's interaction with the product, service, or brand demanded, compared with the number of people who visit a given channel, social media, or website. Chahal and Rani [67] (p. 314) state that "social media brand engagement refers to the participation of customers-physically or psychologically-in varied brand-building activities that impact their decision-making". This is the case of Ryanair, Booking.com, and HolidayCheck, where the number of sales is determined in relation to the number of visits received on the page of a given lodging.…”
Section: Coherence Of Communication Between Online Channels; (2) Veramentioning
confidence: 99%
“…However, there are other indicators, such as engagement, that measure the level of people's interaction with the product, service, or brand demanded, compared with the number of people who visit a given channel, social media, or website. Chahal and Rani [67] (p. 314) state that "social media brand engagement refers to the participation of customers-physically or psychologically-in varied brand-building activities that impact their decision-making". This is the case of Ryanair, Booking.com, and HolidayCheck, where the number of sales is determined in relation to the number of visits received on the page of a given lodging.…”
Section: Coherence Of Communication Between Online Channels; (2) Veramentioning
confidence: 99%
“…In the literature, several studies aimed to find the significant factors affecting customer engagement in brand communities (Jayasingh and Venkatesh, 2015;Carlson et al, 2017;Guo et al, 2017). They focused on various factor types including social factors such as tie strength, trust, social identity, trust and reciprocity (Chahal et al, 2017;Kang et al, 2016;Carlson et al 2017;Tsai et al, 2017;Bohari, 2016), content based factors such as perceived usefulness and perceived enjoyment (Guo et al, 2017;Carlson et al, 2017;Dessart et al, 2015;Chahal et al, 2017), brand related factors such as satisfaction ore brand image (Dessart et al, 2015;Carlson et al, 2017) and customer related factors such as self image enhancement and altruism (Simon et al, 2016;Jahn et al, 2012;Luarn et al, 2016;Marbach et al, 2016). Heinonen (2017) focused on the effect customer based factors on behavioral, emotional and cognitive dimensions of customer engagement.…”
Section: Th Iadis International Conference Information Systems 2019mentioning
confidence: 99%
“…Various social factors have been proposed as drivers of customer engagement (Simon et al, 2016;de Castro, 2017;Luarn et al, 2016;Carlson et al, 2017;Chahal et al, 2017;Huang et al, 2013). Also, Jahn et al (2012) suggested that one most prominent needs of customers is related to content-oriented area which is based on functional and hedonic values.…”
Section: Antecedents Of Customer Engagementmentioning
confidence: 99%
“…Specifically, researches into the concept of 'CBE' have been rapidly developed in the academic marketing literature during the last five to seven years [2] . Key contributions in this area include the development of theoretically related conceptualizations, including 'customer brand engagement' , 'social media engagement' [3] (Hardeep Chahal & Anu Rani, 2017), 'audience engagement' (D Woodford et al, 2015), 'customer engagement behaviors' (Jaakkola & Alexander, 2014), 'brand engagement in self-concept' (Elaine Wallace et al, 2014) and 'social media engagement behavior' (Dolan, Conduit, Fahy, & Goodman, 2016). While the proposed conceptualizations are subject to specific theoretical differences, they predominantly reflect an individual's psychologically-based willingness to invest time in interacting with particular engagement objects (e.g.…”
Section: Introductionmentioning
confidence: 99%